Arsenite‐induced endoplasmic reticulum‐dependent apoptosis through disturbance of calcium homeostasis in HBE cell line. Issue 1 (17th December 2015) - Chen, Chengzhi; Gu, Shiyan; Jiang, Xuejun; Zhang, Zunzhen
ABSTRACT: Calcium (Ca 2+ ) is a ubiquitous cell signal responsible for multiple fundamental cellular functions, including apoptosis. Whether the homeostasis of Ca 2+ is involved in arsenite‐induced apoptosis remains unclear. In this study, we observed that arsenite significantly elevated the intracellular Ca 2+ concentration in a dose‐ and time‐dependent manner. By using the Ca 2+ ‐ATPase inhibitor, thapsigargin, and the inositol 1, 4, 5‐ trisphosphate receptors (IP3Rs) inhibitor, heparin, we further confirmed that the disturbance of endoplasmic reticulum (ER) Ca 2+ homeostasis caused Ca 2+ overload in the cells. Moreover, loss of ER Ca 2+ homeostasis also led to ER stress, mitochondrial dysfunction, and NF‐κB activation. Importantly, pretreatment of cells with heparin remarkably attenuated the elevated cell apoptosis induced by arsenite, but inhibition of ER Ca 2+ uptake with thapsigargin exacerbated arsenite‐induced cell damage significantly. Together, we demonstrated for the first time that arsenite disturbed the Ca 2+ homeostasis in ER, which subsequently led to ER stress, mitochondrial dysfunction, and NF‐κB nuclear translocation, and thus consequently triggering cell apoptosis. Our findings indicate regulation of disrupted Ca 2+ homeostasis in ER may be a potential strategy for prevention of arsenite toxicity. © 2015 Wiley Periodicals, Inc. Environ Toxicol 32: 197–216, 2017.